Diagnostic Yield of Saliva for SARS-CoV-2 Molecular Testing in Children. (26th July 2021) - Banerjee, Dithi; Sasidharan, Anjana; Abdulhamid, Ayah; Orosco, Esmeralda M; Watts, Jennifer L; Schuster, Jennifer E; Myers, Angela L; Weddle, Gina; Selvarangan, Rangaraj
Abstract: Pediatric saliva specimen demonstrated high sensitivity (93%) and specificity (96.2%) compared to paired nasopharyngeal swabs (NPS) by Aptima SARS-CoV-2 Assay (Aptima). Viral loads were comparable in both specimen types. Saliva is a safe, noninvasive, and acceptable alternative specimen for SARS-CoV-2 detection in children.